1999
DOI: 10.1046/j.1471-4159.1999.0721999.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GABA on Melatonin Content in Golden Hamster Retina

Abstract: Abstract:The effect of GABA on melatonin content in vitro was studied in the golden hamster retina. GABA significantly increased melatonin levels in a dose-dependent manner, its effect being reversed by a GABA, receptor antagonist, bicuculline, but not by saclofen, a GABA, antagonist. Moreover, an equimolar concentration of muscimol, a GABA, receptor agonist, significantly increased retinal melatonin content, whereas baclofen, a GABA, receptor agonist, was ineffective. The darknessinduced increase in melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Furthermore, GABA increases melatonin content in a dose-dependent manner in the hamster retina [93]. Our results suggest that GABA could, through membrane hyperpolarization and activation of casein kinase, stimulate the degradation of accumulated PER proteins on the falling phase of their rhythm (which roughly corresponds to the night state), acting to remove feedback inhibition on Per transcription and thereby preparing retinal oscillators for transcriptional activation that characterizes the “day” state.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, GABA increases melatonin content in a dose-dependent manner in the hamster retina [93]. Our results suggest that GABA could, through membrane hyperpolarization and activation of casein kinase, stimulate the degradation of accumulated PER proteins on the falling phase of their rhythm (which roughly corresponds to the night state), acting to remove feedback inhibition on Per transcription and thereby preparing retinal oscillators for transcriptional activation that characterizes the “day” state.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have shown that levels of retinal melatonin are partially regulated by dopamine that acts through a D4 receptor (Jaliffa et al, 2000;Tosini and Dirden, 2000). D4 receptors are negatively coupled with adenylyl cyclase (i.e., their activation decreases the activity of adenlylyl cyclase and thus the levels of cAMP) and therefore is likely that the D4 receptors present in the pineal are also involved in the regulation of pineal melatonin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Many relevant retinal parameters such as GABA (Jaliffa et al 2001), dopamine (Jaliffa et al 2000) and melatonin levels (Faillace et al 1994;Tosini and Menaker 1996) among many others, significantly fluctuate according the time of the day, even under constant lighting conditions, supporting the existence of a retinal circadian clock. However, the cellular location (or possibly multiple locations) of the retinal circadian clock(s) has not been fully identified yet.…”
Section: Discussionmentioning
confidence: 99%
“…Many relevant retinal parameters such as GABA (Jaliffa et al. 2001), dopamine (Jaliffa et al. 2000) and melatonin levels (Faillace et al.…”
Section: Discussionmentioning
confidence: 99%